(untitled) (Research, Society and Development, 2022)
The general objective of the present work is to understand the influence of cognitive and affective aspects on the trajectories of women entrepreneurs in the city of Salgueiro-PE. To this end, four local women entrepreneurs were interviewed, aged between 25 and 30 years, whose interview script was prepared based on the script of the work by Cortez and others, based on the aspects defined by Nassif, Ghobril and Silva, that emphasize the importance of considering affective and cognitive conceptions in the entrepreneur’s action process, considering the initial stage of business, as well as the phase in which companies are established. Data collection took place through a script for conducting a semi-structured interview. It was observed that the entrepreneurs of Salgueiro have their actions influenced by several aspects throughout their entrepreneurial career, such as knowing their limits, perseverance, courage, willpower, initiative, personal motivation, facing challenges, passion for the business and doing what they like. . Both affective and cognitive aspects were found more frequently in the stage of establishment of the enterprise, influencing the decisions of the entrepreneurs.